Association between cardiovascular risk factors and cognitive impairment in adults aged 60 years or older from Chile: a cross-sectional study - Josivaldo Souza-Lima; Sandra Mahecha Matsudo; Pedro Valdivia-Moral; Waldo Pérez; Clemens Drenowatz; Jorge Sapunar Zenteno; Gerson Ferrari (BMC Geriatrics, 2023)
Abstract Background Few studies in Latin America have examined the association between cardiovascular risk factors and cognitive impairment (CI) in a nationally representative sample. Therefore, this study aimed to estimate the prevalence of CI in a nationally representative sample of adults aged 60 years or older from Chile and to investigate the association between cardiovascular risk factors and CI. Methods Data from the cross-sectional 2016–2017 National Health Survey of Chile, which included 2031 adults (63.7% women) was used. Body mass index, metabolic syndrome (blood pressure, triglycerides, fasting glucose or treatment for diabetics, waist circumference, and HDL cholesterol), risk of cardiovascular disease (history and measured variables, using the Framingham risk score), tobacco use, and physical activity were measured. CI was assessed using the Mini-Mental Status Examination (MMSE). Results Overall, the prevalence of CI was 12.2% at the national level. Significant differences in CI were observed by age, education level, risk of cardiovascular disease, and smoking. High risk of cardiovascular disease was associated with higher odds of CI (OR: 2.04; 95%CI: 1.20–3.45) compared to low risk. Smoking was significantly associated with a lower likelihood of CI (OR: 0.56; 95%CI: 0.36–0.87) compared to never smoking. Body mass index, metabolic syndrome, and physical activity were not associated with CI. Conclusions This study provided additional support for previous findings on the relationship between cognitive decline and an elevated risk of cardiovascular disease. Worse CI was associated with the group with the highest risk of cardiovascular disease, and the presence of lifestyle factors, such as obesity and physical inactivity, exacerbate this relationship, but not being a current smoker.